Hurricanes? Let's Make a Move - Nekeisha Spencer; Mikhail-Ann Urquhart (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper establishes the relationship between migration and hurricanes in the Central American and Caribbean region. In contrast to previous studies, we employ hurricane destruction indices to study this relationship. These indices measure geographical destruction which gives us a more comprehensive and accurate view of damage and impact that it has on the movement of people to international destinations. Our estimates reveal that on average hurricane increases migration. We also find that the impact is greater when a hurricane hits a country directly as opposed to not making landfall. These results have policy implications for long term economic growth.
Keywords: 330